2021
DOI: 10.21203/rs.3.rs-137788/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FE Simulation Investigation of Magnesium Alloy by Equal Channel Angular Processing

Abstract: Magnesium alloy is one of the structure metals of great potential. The hcp structure makes its plasticity is poor at room temperature, which severely limits the development of magnesium alloy. Magnesium alloy plastic problem can be resolved through grain refinement method, and equal channel angular processing is one of the more effective methods of grain refinement. In this paper, two-dimensional dynamic simulation of equal channel angular processing for magnesium alloy were done with the finite element softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Magnesium (Mg) is one of the most abundant elements in the world, and its density is only 1.74 g/cm 3 . Due to the excellent properties, such as good machining performance, electromagnetic shielding ability, biocompatibility and recyclability, Mg alloys are considered to be the best potential material for replacing steels and aluminum (Al) alloys in the fields of automotive, aerospace and electronics [1][2][3][4][5]. It has been reported that the addition of lithium (Li) could improve the mechanical properties of Mg alloys and further decrease their densities [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnesium (Mg) is one of the most abundant elements in the world, and its density is only 1.74 g/cm 3 . Due to the excellent properties, such as good machining performance, electromagnetic shielding ability, biocompatibility and recyclability, Mg alloys are considered to be the best potential material for replacing steels and aluminum (Al) alloys in the fields of automotive, aerospace and electronics [1][2][3][4][5]. It has been reported that the addition of lithium (Li) could improve the mechanical properties of Mg alloys and further decrease their densities [6].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, for the preparation of chemical conversion surface films, the category of additive in surfactants plays an important role, and their inhibiting effect on corrosion development has been widely studied [8]. Generally, the main functions of additives consist of the following: (1) promoting the formation of a coating film; (2) reducing particle crystallinity; (3) controlling the conversion rate; (4) increasing the hydrophobicity of the metal surface; and (5) enhancing the solubility of the main components of the conversion fluid in water [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%